Study on load-bearing behaviors of prestressed post-grouting tubular piles in the karst region of northern Fujian Province, China - Huang, Lingjun; Gao, Rui; Chi, Jingou; Yan, Xiaocai (Frontiers in Earth Science, 2024)
This paper discusses the load-bearing behaviors of post-grouting tubular piles in karst region of north Fujian Province with reference to the prestressed tubular piles adopted in the residential buildings of Haixi Comprehensive Trade City Phase II Project in Sanming City. The load-settlement curve, pile side friction resistance, and pile end resistance of tubular piles are analyzed by finite element numerical simulations and field static load tests. The load-bearing behaviors of prestressed tubular piles under karst geological conditions with two different spatial features are comparatively investigated, and the effectiveness of tubular pile reinforcement is verified by field settlement observation. The results reveal that the finite element numerical model can effectively simulate the tubular pile-soil interaction. The use of pile end post-grouting of prestressed tubular piles in the karst region can significantly increase their load-bearing capacities. The top settlements of grouted tubular piles under the maximum test load can be reduced by 16.8%-22.3% compared with these of ungrouted test piles, and the theoretical simulated ultimate load-bearing capacity can be increased by 27.3%. The adoption of pile end post-grouting technique can reduce the pile end displacement of tubular piles and improve the proportion of pile end resistance. Plastic-hard plastic breccia silty clay can be used as a bearing stratum for post-grouting to achieve excellent grouting performance. The bead-shaped karst caves are more unfavorable to the exertion of load-bearing capacity of the tubular piles than the karst caves filled with plastic-hard plastic breccia silty clay to which the piles have direct access.The field monitored average settlements of the 19# and 17# buildings under karst geological conditions with two different spatial features are -12.88 mm and -8.98 mm, respectively, both of which do not exceed the warning value, indicating that it is feasible for the project to adopt the pile end post-grouting technique of the tubular piles. The achievements of this study help to further reveal the load-bearing mechanism of this type of pile, which can provide a basis for its engineering design and construction optimization.